2003
DOI: 10.1074/jbc.m302004200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent Kinase-5 Is Involved in Neuregulin-dependent Activation of Phosphatidylinositol 3-Kinase and Akt Activity Mediating Neuronal Survival

Abstract: The phosphatidylinositol 3-kinase (PI3K)/Akt signaling pathway plays an important role in mediating survival signals in wide variety of neurons and cells. Recent studies show that Akt also regulates metabolic pathways to regulate cell survival. In this study, we reported that cyclin-dependent kinase-5 (Cdk5) regulates Akt activity and cell survival through the neuregulin-mediated PI 3-kinase signaling pathway. We found that brain extracts of Cdk5؊/؊ mice display a lower PI 3-kinase activity and phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 73 publications
7
119
0
Order By: Relevance
“…247 In OVCAR3 cells, EGF led to activation of all four ERBB family members, but in the cell line OAW42, lacking ERBB3, EGF did not activate ERBB4 and NRG activated ERBB4 only after long exposure. These results indicate, for ovarian cancer cells, a central role for ERBB3 in activation of ERBB4, and suggest that ERBB3 itself is activated by a path other than the other ERBB receptors, either its own very weak kinase activity, or by recruitment of some other kinase known to increase its activation, such as PTK6 125 or c-SRC. 126 Another intriguing observation was the presence of truncated ERBB3 transcripts of 1.6, 1.7, 2.1 and 2.3 kb in ovarian carcinoma cells lines.…”
Section: Ovarian Cancermentioning
confidence: 66%
See 2 more Smart Citations
“…247 In OVCAR3 cells, EGF led to activation of all four ERBB family members, but in the cell line OAW42, lacking ERBB3, EGF did not activate ERBB4 and NRG activated ERBB4 only after long exposure. These results indicate, for ovarian cancer cells, a central role for ERBB3 in activation of ERBB4, and suggest that ERBB3 itself is activated by a path other than the other ERBB receptors, either its own very weak kinase activity, or by recruitment of some other kinase known to increase its activation, such as PTK6 125 or c-SRC. 126 Another intriguing observation was the presence of truncated ERBB3 transcripts of 1.6, 1.7, 2.1 and 2.3 kb in ovarian carcinoma cells lines.…”
Section: Ovarian Cancermentioning
confidence: 66%
“…121,122 It may be that other pathways could also be involved: erlotinib-sensitive lung carcinoma cells expressed higher levels of the SRC-like kinase BRK; BRK is known to phosphorylate ERBB3 and promote PI3 kinase AKT signaling in mammary cells. 125 In addition, ERBB3 can be targeted independently of EGFR and ERBB2, as recently shown for the marine-derived anti-tumor agent kahalalide F. 428 In short, ERBB3 not only participates in the sensitivity of the majority of lung cancers that respond to EGFR tyrosine kinase inhibitors, but also in other malignancy-associated signaling paths. These multiple facets increase its attractiveness as a molecular target for therapy in this type of cancer.…”
Section: Erbb3 Egfr Mutation and Clinical Responsiveness To Egfr Inhmentioning
confidence: 93%
See 1 more Smart Citation
“…19 Cdk5 knockout mice show inhibition of the PI3K/Akt pathway in neurons. 12 Cdk5 phosphorylates the neuregulin receptor ErbB2/3 and thus is involved in neuregulin-induced Akt activity and neuregulin-mediated neuronal survival. 12 An earlier study indicated that Akt phosphorylates Bad, a Bcl-2 family member, for cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…12 Cdk5 phosphorylates the neuregulin receptor ErbB2/3 and thus is involved in neuregulin-induced Akt activity and neuregulin-mediated neuronal survival. 12 An earlier study indicated that Akt phosphorylates Bad, a Bcl-2 family member, for cell survival. 36 In this study, we have shown that BDNF-induced Cdk5 kinase activity upregulated Bcl-2 during the neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%